Essential Oil of Croton zehntneri and Its Main Constituent Anethole Block Excitability of Rat Peripheral Nerve - da Silva-Alves, Kerly Shamyra; Ferreira-da-Silva, Francisco Walber; Coelho-de-Souza, Andrelina Noronha; Albuquerque, Aline Alice Cavalcante; do Vale, Otoni Cardoso; Leal-Cardoso, José Henrique (Planta Medica, 2015)
Croton zehntneri is an aromatic plant native to Northeast Brazil and employed by local people to treat various diseases. The leaves of this plant have a rich content of essential oil. The essential oil of C. zehntneri samples, with anethole as the major constituent and anethole itself, have been reported to have several pharmacological activities such as antispasmodic, cardiovascular, and gastroprotective effects and inducing the blockade of neuromuscular transmission and antinociception. Since several works have demonstrated that essential oils and their constituents block cell excitability and in view of the multiple effects of C. zehntneri essential oil and anethole on biological tissues, we undertook this investigation aiming to characterize and compare the effects of this essential oil and its major constituent on nerve excitability. Sciatic nerves of Wistar rats were used. They were mounted in a moist chamber, and evoked compound action potentials were recorded. Nerves were exposed in vitro to the essential oil of C. zehntneri and anethole (0.1–1 mg/mL) up to 180 min, and alterations in excitability (rheobase and chronaxie) and conductibility (peak-to-peak amplitude and conduction velocity) parameters of the compound action potentials were evaluated. The essential oil of C. zehntneri and anethole blocked, in a concentration-dependent manner with similar pharmacological potencies (IC50: 0.32 ± 0.07 and 0.22 ± 0.11 mg/mL, respectively), rat sciatic nerve compound action potentials. Strength-duration curves for both agents were shifted upward and to the right compared to the control curve, and the rheobase and chronaxie were increased following essential oil and anethole exposure. The time courses of the essential oil of C. zehntneri and anethole effects on peak-to-peak amplitude of compound action potentials followed an exponential decay and reached a steady state. The essential oil of C. zehntneri and anethole caused a similar reduction in conduction velocities of the compound action potential waves investigated. In conclusion, we demonstrated here that the essential oil of C. zehntneri blocks neuronal excitability and that this effect, which can be predominantly attributable to its major constituent, anethole, is important since these agents have several pharmacological effects likely related to the alteration of excitability. This finding is relevant due to the use of essential oils in aromatherapy and the low acute toxicity of this agent, which exhibits other effects of potential therapeutic usefulness.
Keywords: Croton zehntneri; Euphorbiaceae; essential oil; anethole; extracellular recording; sciatic nerve; neuronal excitability